Peran Strategis Kurikulum PAUD dalam Kesiapan Sekolah Anak - Kamelia Olga Litna; Yohana Yuniati; Gokma N. Tampubolon (Fakultas Pendidikan, Universitas Sultan Muhammad Syafiuddin Sambas, 2025)
This study aims to examine the role of the early childhood education curriculum in supporting children's school readiness. The method used in this research is a literature review. The author collected various documents and research articles related to early childhood education curriculum and school readiness. School readiness is a key foundation for children's success in formal education. The Early Childhood Education curriculum plays an important role in supporting children's school readiness. The main approach in early childhood education curriculum is play-based and child-centered learning. A well-designed early childhood education curriculum not only focuses on academic aspects but also develops social, emotional, physical, and cognitive skills holistically. A play-based and child-centered curriculum significantly contributes to children's readiness for primary school.